ZAKAT AND MAQASID SHARI'AH: ENSURING EFFECTIVE SUPPORT FOR THE NEEDY - Sulastri, Widia; Efendi, Faisal; Razak, Dudung Abdul; Rahmita, Rahmita; Kapitri, Neneng (Universitas Syiah Kuala, 2024)
This article investigates the distribution of zakat from agricultural products in Nagari Punggasan, West Sumatra. It employs a normative empirical method, analyzing legal provisions through a sociological and jurisprudential lens. Empirically, the study focuses on practices observed in Nagari Punggasan. The distribution of zakat from crops is calculated based on the capital utilized from the onset of cultivation until the harvest. Once the harvest is complete and the funds have been disbursed, the zakat obligation is considered fulfilled. This distribution process involves inviting all relevant community members, including Ninik Mamak, Labai, Imams, Khatibs, widows, and affluent individuals.However, this practice raises concerns regarding its alignment with Islamic teachings, particularly Surah At-Taubah, verse 60, which outlines the rightful recipients of zakat. According to the principles of Maqasid Shari'ah, the purpose of Shari'ah is to benefit humanity, ensuring both the spiritual and physical well-being of individuals and society at large. The objectives of Maqasid Shari'ah emphasize the importance of respecting the rights of the asnaf (eligible recipients) who are entitled to receive zakat.